2021
DOI: 10.48550/arxiv.2106.05250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The zero-rate threshold for adversarial bit-deletions is less than 1/2

Abstract: We prove that there exists an absolute constant δ > 0 such any binary code C ⊂ {0, 1} N tolerating (1/2 − δ )N adversarial deletions must satisfy |C| 2 poly log N and thus have rate asymptotically approaching 0. This is the first constant fraction improvement over the trivial bound that codes tolerating N/2 adversarial deletions must have rate going to 0 asymptotically. Equivalently, we show that there exists absolute constants A and δ > 0 such that any set C ⊂ {0, 1} N of 2 log A N binary strings must contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In a recent work, Guruswami, He, and, Li [GHL21] strengthened this result for binary codes and showed that there exists an absolute constant δ such that any binary code C ⊆ {0, 1} n (not only linear) that can decode from (1/2 − δ) fraction of deletions must satisfy |C| ≤ 2 poly log n . In particular, we cannot hope to decode a fraction of insdel errors arbitrarily close to 1/2 with codes of positive rate.…”
Section: Previous Resultsmentioning
confidence: 92%
“…In a recent work, Guruswami, He, and, Li [GHL21] strengthened this result for binary codes and showed that there exists an absolute constant δ such that any binary code C ⊆ {0, 1} n (not only linear) that can decode from (1/2 − δ) fraction of deletions must satisfy |C| ≤ 2 poly log n . In particular, we cannot hope to decode a fraction of insdel errors arbitrarily close to 1/2 with codes of positive rate.…”
Section: Previous Resultsmentioning
confidence: 92%